2007
DOI: 10.1002/biof.5520310310
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and leptin up‐regulate extracellular matrix production by dermal fibroblasts

Abstract: Adipocytes were recently shown to secrete adipocytokines, such as adiponectin and leptin, which may have an endocrine role. Subcutaneous adipose tissue lies just beneath the dermis, and dermal condition is correlated with body mass index (BMI). However, it is not clear whether adipocytokines released by adipocytes in subcutaneous adipose tissue influence the adjacent dermis. We found that human dermal fibroblasts express genes encoding receptors for adiponectin and leptin, and that those cytokines both signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 26 publications
0
67
1
1
Order By: Relevance
“…On the other hand, our results showed no significant difference in the number of macrophages in subcutaneous adipose tissue between the control and obesity groups on the day before wounding. This result differed from previous and up-regulating collagen production by dermal fibroblasts [44]. In this study, we did not observe the blood leptin concentration on the day before wounding.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, our results showed no significant difference in the number of macrophages in subcutaneous adipose tissue between the control and obesity groups on the day before wounding. This result differed from previous and up-regulating collagen production by dermal fibroblasts [44]. In this study, we did not observe the blood leptin concentration on the day before wounding.…”
Section: Discussioncontrasting
confidence: 99%
“…22 Moreover, adiponectin upregulates the ECM production by dermal fibroblasts. 23 All these findings suggest that adiponectin may affect collagen homeostasis via different mechanisms in the various tissues. Therefore, we were interested in the effect of adiponectin overexpression on the stability of preexisting plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Dermal fibroblasts are the dominant players in the process of granulation tissue formation during cutaneous wound healing. Recent reports have revealed that adiponectin induces proliferation of dermal fibroblasts and upregulation of collagen production (47,48). Furthermore, adiponectin induces proliferation of HUVECs and stimulates angiogenesis (10), indicating the positive contribution of adiponectin to optimal wound repair.…”
Section: Discussionmentioning
confidence: 99%